Fiscal policy and its impact on reducing the budget deficit during the period (2000-2020) - Case study of the resource control fund in Algeria - Saib, fodil; bouchama, Mustapha (Journal of Research in Finance and Accounting, 2022)
Most developing countries suffer from budget deficits due to their lack of economic resources, low levels of national income, per capita income, limited revenues, and increased public expenditures. Since Algeria is characterized by these same features, this study aims to highlight the impact of fiscal policy in reducing the budget deficit. A resource control fund was established in 2000 to reduce the deficit. It succeeded in paying off Algeria's external debt as well as financing the deficit through the state's fiscal policy tools which effectively achieved the fiscal balance and budget deficit reduction, in addition to reaching economic stability and the state’s general objectives. The study concluded that fiscal deficits have a positive impact on public consumption, public savings, capital formation, national income, and domestic output, and internal and external indebtedness, but have no impact on economic growth.